Structural analogs of huperzine A improve survival in guinea pigs exposed to soman - Gunosewoyo, Hendra; Tipparaju, S.; Pieroni, M.; Wang, Y.; Doctor, B.; Nambiar, M.; Kozikowski, A. (Pergamon, 2013)
Chemical warfare nerve agents such as soman exert their toxic effects through an irreversible inhibition of acetylcholinesterase (AChE) and subsequently glutamatergic function, leading to uncontrolled seizures. The natural alkaloid (-)-huperzine A is a potent inhibitor of AChE and has been demonstrated to exert neuroprotection at an appropriate dose. It is hypothesized that analogs of both (+)- and (-)-huperzine A with an improved ability to interact with NMDA receptors together with reduced AChE inhibition will exhibit more effective neuroprotection against nerve agents. In this manuscript, the tested huperzine A analogs 2 and 3 were demonstrated to improve survival of guinea pigs exposed to soman at either 1.2 or 2 × LD50.